Host‐ and stage‐dependent secretome of the arbuscular mycorrhizal fungus Rhizophagus irregularis. (17th April 2018) - Zeng, Tian; Holmer, Rens; Hontelez, Jan; te Lintel‐Hekkert, Bas; Marufu, Lucky; de Zeeuw, Thijs; Wu, Fangyuan; Schijlen, Elio; Bisseling, Ton; Limpens, Erik
Summary: Arbuscular mycorrhizal fungi form the most wide‐spread endosymbiosis with plants. There is very little host specificity in this interaction, however host preferences as well as varying symbiotic efficiencies have been observed. We hypothesize that secreted proteins (SPs) may act as fungal effectors to control symbiotic efficiency in a host‐dependent manner. Therefore, we studied whether arbuscular mycorrhizal (AM) fungi adjust their secretome in a host‐ and stage‐dependent manner to contribute to their extremely wide host range. We investigated the expression of SP‐encoding genes of Rhizophagus irregularis in three evolutionary distantly related plant species, Medicago truncatula, Nicotiana benthamiana and Allium schoenoprasum . In addition we used laser microdissection in combination with RNA‐seq to study SP expression at different stages of the interaction in Medicago. Our data indicate that most expressed SPs show roughly equal expression levels in the interaction with all three host plants. In addition, a subset shows significant differential expression depending on the host plant. Furthermore, SP expression is controlled locally in the hyphal network in response to host‐dependent cues. Overall, this study presents a comprehensive analysis of the R . irregularis secretome, which now offers a solid basis to direct functional studies on the role of fungal SPs in AM symbiosis.